EVALUATION STYLES IN THE PROFESSIONAL CAREER OF MATHEMATICAL SCIENCES AND INFORMATICS OF THE FACULTY OF EDUCATION - Espinoza Espinoza, Alex (2023)
The objective of this research work is to identify the relationship between the evaluation paradigms, the evaluation of the teaching-learning process and the relationship between the types of evaluation, in students of the Professional Career of Mathematical Sciences and Informatics of the Faculty of Education of the National University of Central Peru. For this purpose, we worked on a population of 250 students distributed over five academic semesters, from which a sample of 95 students was obtained, to whom validated questionnaires and rubrics were applied. The research design was correlational. The results are significant between the paradigms and types of evaluation that are developed at the university level taking into account academic performance and its relationship with the National Basic Education Curriculum and the evaluation system of the National University of Central Peru.